2016
DOI: 10.1021/acs.inorgchem.6b00522
|View full text |Cite
|
Sign up to set email alerts
|

Metal–Organic Framework Based on Isonicotinate N-Oxide for Fast and Highly Efficient Aqueous Phase Cr(VI) Adsorption

Abstract: Synthesis of new porous materials has been developed for efficient capture of pollutants in environmental sciences. Here, the application of a new metal-organic framework (TMU-30) has been reported based on isonicotinate N-oxide as an adsorptive site for fast and highly efficient aqueous phase adsorption of Cr(VI). The adsorption process showed no remarkable effect over a pH range of 2-9. The maximum capacity of the adsorption was reached in just less than 10 min and followed the pseudo-second-order kinetics. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
46
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 116 publications
(48 citation statements)
references
References 50 publications
2
46
0
Order By: Relevance
“…S15). S16), 47,48 verifying the guess. The presence of Cr(VI) species was confirmed by FT-IR spectroscopy.…”
Section: Cr(vi) Uptake Kinetics and Isothermmentioning
confidence: 82%
“…S15). S16), 47,48 verifying the guess. The presence of Cr(VI) species was confirmed by FT-IR spectroscopy.…”
Section: Cr(vi) Uptake Kinetics and Isothermmentioning
confidence: 82%
“…Herein, Morsali et al. reported a new 3D framework, [Pb(INO) 2 ] 2 (TMU‐30), based on INO consisting of 1D channels . Because of the N‐Oxide group's positive charge, electrostatic interactions with chromate ions will be generated.…”
Section: Adsorption Of One Metal Ionmentioning
confidence: 99%
“…Herein, Morsali et al reported a new 3D framework, [Pb(INO) 2 ] 2 (TMU-30), based on INO consisting of 1D channels. [6] Because of the N-Oxide group's positive charge, electrostatic interactions with chromate ions will be generated. They observed that TMU-30 adsorbed all existing species of Cr VI including HCrO 4 À and CrO 4 2 À over a wide pH range (2 À 9), but the crystalline structure of TMU-30 starts to collapse in pH > 9.…”
Section: Chromiummentioning
confidence: 99%
See 2 more Smart Citations